2019
DOI: 10.1111/apt.15365
|View full text |Cite
|
Sign up to set email alerts
|

Significant reduction in heart rate variability is a feature of acute decompensation of cirrhosis and predicts 90‐day mortality

Abstract: Background: Heart rate variability (HRV) is reduced in cirrhosis and in conditions of systemic inflammation. Whether HRV is associated with cirrhosis decompensation and development of acute-on-chronic liver failure (ACLF) is unknown.Aims: To (a) validate wireless remote HRV monitoring in cirrhosis decompensation;(b) determine if severely reduced HRV is a surrogate for inflammation and progression of cirrhosis decompensation; (c) assess if measuring HRV determines prognosis in cirrhosis decompensation. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…These results also extend our knowledge about the potential application of physio-markers in the clinical assessment of patients with cirrhosis (Mani et al, 2009;Montagnese, De Rui, et al, 2015;Montagnese, Jackson, & Morgan, 2007;Olesen et al, 2016). There has been an interest in recent years in the application of HRV for monitoring patients with cirrhosis awaiting liver transplantation (Bhogal et al, 2019;Bhogal, Montagnese, & Mani, 2018;Chan, Yeh, & Sun, 2017;Jansen et al, 2019;Xiong, Faes, & Ch, 2017). However, this study reveals that HRV is not the Note: MELD score was significant in the analysis when compared with the other variables listed in Cox bivariate regression analysis.…”
Section: Discussionsupporting
confidence: 71%
“…These results also extend our knowledge about the potential application of physio-markers in the clinical assessment of patients with cirrhosis (Mani et al, 2009;Montagnese, De Rui, et al, 2015;Montagnese, Jackson, & Morgan, 2007;Olesen et al, 2016). There has been an interest in recent years in the application of HRV for monitoring patients with cirrhosis awaiting liver transplantation (Bhogal et al, 2019;Bhogal, Montagnese, & Mani, 2018;Chan, Yeh, & Sun, 2017;Jansen et al, 2019;Xiong, Faes, & Ch, 2017). However, this study reveals that HRV is not the Note: MELD score was significant in the analysis when compared with the other variables listed in Cox bivariate regression analysis.…”
Section: Discussionsupporting
confidence: 71%
“…Reduced heart rate variability is a common feature of cirrhosis due to systemic inflammation. Heart rate variability is further reduced in patients developing ACLF and can be used to predict disease progression and short-term mortality (45). Interestingly, mincle is also expressed in cardiac tissue (46).…”
Section: Discussionmentioning
confidence: 99%
“…7 8 47 However, to date, no immunopathological studies performed in patients with AD or ACLF providing robust support to this hypothesis are available. Still, some studies showed that liver-derived systemic inflammatory markers are associated with the development of organ failures and especially cardiac dysfunction 48 49…”
Section: Pathophysiology Of Ad and Aclfmentioning
confidence: 99%